Uso de diferentes herbicidas pré emergentes em diferentes períodos de aplicação e seus possíveis efeitos residuais na cultura do milho - Bernardino, Eric Matheus (2023)
The production of corn (Zea mays) in Brazil is the third largest in the world, and of great global importance, as it is the largest exporter of the crop. With the increase in the areas for production, the number of researches with herbicide positioning has been growing. The use of pre-emergence for corn is becoming more common, due to the great competition of weeds during the initial stages of the crop, besides giving security to the farmer and a possible decrease in the number of post-emergence applications, with lower costs for the crop. In this sense, this work aimed to evaluate the efficiency of different pre-emergents in the weed seed bank, and possible effects on the development and productivity of corn. The work was conducted at the premises of the Universidade Tecnológica Federal do Paraná Campus Dois Vizinhos, in a bifatorial scheme, in randomized block design (DBC). The treatments used were composed of three different herbicides, namely: Imazetapir, SMetalochlor and Triflularin, in three different application periods, being them 55, 40 and 25 days before sowing. The weed control (%), weed count and identification, corn height, number of leaves and ear insertion height were evaluated. Through the data obtained it was concluded that the pre-emergent herbicides had a positive effect on weed control overall, compared to the control plots. Some of them, such as black prickly pear, Guanxuma and millet, showed an effective control overall. Turnip and Rape were better controlled with Imazetapir, as well as bitter grass and millet, which were better controlled with Trifluralin. The most effective control occurred in plots where the treatments were applied 25 days before sowing. Regarding residual effects on corn, a decrease in the height of the ear insertion and of the whole plant was observed, compared to the other treatments, in the plots of the Imazetapir treatment applied 25 days in pre-sowing.